Tinjauan Kebijakan Pertahanan Indonesia di Kepulauan Natuna Dihadapkan dengan Perkembangan Pembangunan Pangkalan Militer China - Achyar, Muhammad; Wayan Midhio, I; Khaerudin, Khaerudin (CV RIFAINSTITUT, 2021)
The purpose of this study is to analyze the strategies and constraints of Indonesia's defense policy in responding to the development of China's military base construction in the South China Sea. Data obtained through literature study and interviews with informants, then analyzed using qualitative methods. The results of this study can be concluded that Indonesia's current defense strategy has not been concretely described and the problems found in the formulation of Indonesian policies have yet to be found a solution because there are still egos and differences in interests among policy makers, the solution requires commitment from the Ministry of Defense, TNI Headquarters, and Main Command to faithfully adhere to execute all planning and road map that were prepared together.